Effect of Calcium Sources and Particle Size on Performance and Eggshell Quality in Laying Hens - Arzu Erol Tunç; Yusuf CUFADAR (Turkish Journal of Agriculture: Food Science and Technology)
An experiment was conducted to determine the effect of different combination calcium sources and particle size on performance and egg shell quality in layer hens. In the experiment, 198 brown laying hens at 44 week of age were randomly assigned into 11 treatments groups. The experimental diets consisted of different calcium sources (Fine limestone, large limestone, large oyster shell and large egg shell) and their different combination. The experimental unit consisted of a groups of three hens, thus each treatment was replicated six times. Different calcium sources and particle size addition to the laying hens diet had no significantly effect on body weight gain, egg production, egg mass, feed intake, feed conversion ratio, egg specific gravity, egg shell weight, egg shell thickness and egg shell breaking strength but egg weight had significantly affected by the treatments. The significantly highest egg weight was found in laying hens fed with 50 % fine limestone and 50 % large limestone. Dietary different Ca sources had a significant effect on Ca, P and Mg as mineral contents of eggshell and tibia. In the present study, when dietary large calcium sources (limestone, oyster shell and egg shell) had no effect on performance and eggshell quality parameters in laying hens. However, dietary containing at least 50 % large calcium sources had positive effect on mineral contents of tibia.